Literature Study: The Role of Health Cadres in Stunting Prevention to Support the Realisation of Sustainable Development Goals (SDG's) - Purba, Anita Zahra Putri; Siregar, Annisa Rizki Ramadani; Panjaitan, Nuraisyah Wulandari; Purba, Sri Hajijah (Universitas Ibn Khaldun Bogor, 2024)
Introduction: Stunting is one of the chronic nutritional problems of global concern, including in the Sustainable Development Goals (SDG's) agenda. In Indonesia, stunting is still a major health problem and contributor to child morbidity and mortality. To overcome this problem, prevention efforts are needed that involve various parties, including health cadres at the community level. This study aims to analyze the role of health cadres in stunting prevention to support the realization of the Sustainable Development Goals (SDG's). Methods: This study used a literature study by collecting and reviewing previous research, especially looking for information about the involvement of the role of health cadres in stunting prevention. Results: Health cadres have a role and function as the main driver at the community level to provide education, monitor children's nutritional status, and conduct nutrition intervention activities. Through increased capacity and knowledge, health cadres can help reduce the prevalence of stunting and support the achievement of the SDGs, namely ending hunger and ensuring healthy lives and well-being for all. Conclusion: Support and commitment from all parties are needed to strengthen the role of health cadres in supporting the realization of the SDGs. With the right support and good collaboration, this program can have a significant impact in improving the health and welfare of the community.